THE IMPACT OF THE CONTRIBUTION OF THE MINING AND QUARRYING SECTOR AND THE PROCESSING INDUSTRY ON ECONOMIC GROWTH IN BENGKALIS REGENCY 2011-2024 - Della Novita Sari; Melani Noviantori Ramadhan; Farraz Yuni Syafitri; Wiwi Jupiani; Misdawita Misdawita (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study aims to analyze the influence of the mining and quarrying sector and the manufacturing industry sector on economic growth in Bengkalis Regency for the period 2011–2024. Economic growth is measured using Gross Regional Domestic Product (GRDP) at constant prices which describes the real economic performance of the region. This study uses a quantitative method with a descriptive approach and multiple linear regression analysis, based on secondary data obtained from the Central Statistics Agency (BPS) of Bengkalis Regency. The results of the analysis show that partially, the mining and quarrying sector has a significant effect on economic growth with a significance value of 0.000 < 0.05. Conversely, the manufacturing industry sector does not have a significant effect with a significance value of 0.539 > 0.05. Simultaneously, both sectors have a significant effect on economic growth with a significance value of 0.000 < 0.05 and an Adjusted R² value of 0.926, which means that 92.6% of the variation in economic growth can be explained by these two sectors. These findings indicate that the economy of Bengkalis Regency is still dominated by mining and quarrying sector activities, while the manufacturing industry sector has not provided an optimal contribution to regional economic growth. Therefore, a strategy is needed to strengthen the processing industry sector through investment, technological innovation, and downstream development so that the regional economic structure becomes more balanced and sustainable.